Costos de producción de la Industria Arrocera Alta Gracia S.A de la ciudad de Guayaquil, periodo 2022. - Aguilar Morán, Denisse Paola (2024)
The Alta Gracia S.A. Rice Industry, based in Guayaquil, Ecuador, faces the constant challenge of efficiently managing its production costs to maintain competitiveness in the market. In the 2022 period, the company sought to optimize its processes and resources to improve profitability. This study focused on analyzing the production costs of the company during this period. Various elements that make up these costs were identified, including raw materials, labor, fixed and variable costs, among others. A comprehensive breakdown of these components was carried out, allowing for a better understanding of the company's cost structure and the factors that influence it. Additionally, variations in costs throughout the year were analyzed, considering factors such as changes in input prices, fluctuations in market demand, and climatic events. Based on these analyses, strategic recommendations were formulated to improve operational efficiency and profitability of the Alta Gracia S.A. Rice Industry in the future.